SnO2 THIN FILM DEPOSITION FOR N-TYPE AND WINDOW OF CIS SOLAR CELL - Sri Sulamdari; Yunanto Yunanto (Jurnal Sains Materi Indonesia, 2008)
SnO2 THIN FILM DEPOSITION FOR N-TYPE AND WINDOW OF CIS SOLAR CELL. SnO2 thin film deposition on glass substrate has been carried out using DC sputtering technique. This research has purpose to find the three sputtering parameters such as deposition time, pressure of Ar gas and substrate temperature. By controlling these parameters, it is expected that the SnO2 thin film has low resistivity and high transmittance which can be used for the CIS solar cell. Ar ion bombarded on SnO2 target, placed on the vacuum chamber, hence the sputtered SnO2 target atom forms the SnO2 thin film on glass substrate. The resistivity and conduction type were measured using four point probe, the transmittance by UV-Vis and the crystal structure by XRD. The microstructure and thickness were observed using SEM, while the chemical composition using EDS. The results show that the lowest resistivity with N conduction type is 5 x 10-2 ohm.cm, the highest transmittance is 83.59 % at λ = 600 nm, the grains are distributed homogeneously, the thickness of thin film is 1 μm, the crystal structure of SnO2 thin film is tetragonal while composition of thin film consists of 38.42 % Sn atom, 60.96 % O atom, and 2.61 % Fe atom.